Deep inelastic cross-section measurements at large y with the ZEUS detector at HERA - Abramowicz, H; Abt, I; Adamczyk, L; Adamus, M; Aggarwal, R; Antonelli, S; Arslan, O; Aushev, V; Aushev, Y; Bachynska, O; Barakbaev, A; Bartosik, N; et al. (American Physical Society, 2014)
The reduced cross sections for e+p deep inelastic scattering have been measured with the ZEUS detector at HERA at three different center-of-mass energies, 318, 251 and 225 GeV. The cross sections, measured double differentially in Bjorken x and the virtuality, Q2, were obtained in the region 0.13≤y≤0.75, where y denotes the inelasticity and 5≤Q2≤110GeV2. The proton structure functions F2 and FL were extracted from the measured cross sections.